HUBUNGAN PENGETAHUAN KELUARGA TENTANG PRE OPERASI DENGAN TINGKAT KECEMASAN KELUARGA PADA KLIEN PRE OPERASI - Nugroho, Christianto (Jurnal AKP, 2012)
Pre operationÂ  represent an act that must be done before the operation of client. Period of Pre operation represent a time whenÂ  an increasing anxiety for client and his family. Lack of knowledge is able to trigger an anxiety, the better the level of knowledge, can decreases anxiety and otherwise, the lack of knowledge would increase the level of anxiety. The purpose of this study is to relation determine of family knowledge about pre operation with the level of family anxiety at client pre operation in Seruni room RSUD Unit Swadana Pare Kediri.Research design used cross sectional analytic that is research type that emphasizes at period of measurement or observation of independent and dependent variable data only once at a time, with a population of 23 people pre operation, use a purposive sampling technique, and samples amount toÂ  22 people. Intake of data use questionnaire conducted on 5 May - 20 May 2010. After the data were analyzed with Spearman rho test with significance value Î± (0.05).The research results obtained that is Ï (0.009) <Î± (0.05) this means that Ho is rejected, H1 accepted so there is a correlation between a family knowledge about pre operation with the level of family anxiety at client of pre operationÂ  in Seruni Room RSUD Pare Unit Swadana Pare Kediri.From result of research, anxiety is influenced by knowledge or information, information is an important function in reducing the anxiety that can decrease anxiety.